PENGARUH CREATIVE PSYCHOLOGY CAPITAL MEMEDIASI SENSITIVITAS ETIS TERHADAP JOB PERFORMANCE - Syaikhul Falah (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2018)
This study aims to analyze the psychological aspects (creative psychology capital and ethical sensitivity) to the performance. This research was conducted in several hospitals in Jayapura City. Data collection in this research is using questionnaire where respondent in this research is staff of finance or administration and program. The sampling technique used in this research is census sampling method. The number of research samples taken as many as 38 respondents. This research uses Partial Least Square (PLS) analysis technique. The result of this study shows that the developed hiptotesi significantly influence the performance. Keywords: Psychological Capital, Ethical Sensitivity and Job Performance, hospital